ТЕАТР – МӘНАЎИЙ ДҮНЬЯМЫЗДЫ ТӘРБИЯЛАЎ ҚУРАЛЫ СЫПАТЫНДА - Юсупов, Қ.Б. (ILIM hám JÁMIYET, 2021)
The article discusses the period of formation of the Karakalpak theater and its peculiarities, scientific-historical-philosophical views on the development of the national theater, which led to the emergence of new cultural views of the people.